Central Obesity as a Major Determinant of Body Image Concerns: A Comparative Study Between Egyptian and Lebanese University Females - Germine El-Kassas; Nour Kabbara; Fouad Ziade (Journal of Nutrition and Metabolism)
Conclusions: The study findings call for tailored, culture-specific intervention programs that enable students to improve their self-acceptance and lead a healthy life.